A difusão gastronômica no espaço folkcomunicacional (Revista Internacional de Folkcomunicação, 2011)
Abstract: In order to guide folk communication researchers into the popular communication processes, Luiz Beltrão, the founding father of folk communication as an academic discipline, pointed out that cooking is a “relevant home arts”, explaining how gastronomy has been disseminated worldwide, gaining recognition and legitimacy.